Efektivitas Ekstrak Lada Hitam (Piper nigrum L) Terhadap Jumlah dan Motilitas Spermatozoa - Puji Fauziyyah Iskandar (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Infertility is a major problem in married couples and 40% is caused by malefactors. This is caused by an increase in reactive oxygen species (ROS) which can affect the quantity and quality of spermatozoa so that there is a change in the number and motility of the spermatozoa produced. Objective: To determine the effectiveness of black pepper extract (Piper nigrum L) on the number and motility of spermatozoa. Method: using literature studies from various sources of national and international journals by summarizing the discussion, and comparing the results presented in these various sources. Result: black pepper has the main content of piperine which acts as an antioxidant. Piperine can also increase gonadotropin hormones, especially luteinizing hormone (LH) which will stimulate the formation of spermatozoa or the process of spermatogenesis so that it affects the number and motility of spermatozoa. Conclusion: Giving black pepper extract has an effect on the number and motility of spermatozoa